2009
DOI: 10.1200/jco.2008.19.2930
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sequential High-Dose Doxorubicin and Ifosfamide Compared With Standard-Dose Doxorubicin in Patients With Advanced Soft Tissue Sarcoma: An Open-Label Randomized Phase II Study of the Spanish Group for Research on Sarcomas

Abstract: Single-agent doxorubicin remains the standard treatment in fit patients with advanced soft tissue sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 18 publications
2
51
0
4
Order By: Relevance
“…Performance status is a well-known prognostic factor of metastatic soft tissue sarcoma in general (Van Glabbeke et al, 1999;Maurel et al, 2009;Kroep et al, 2011). In other literature (Van Glabbeke et al, 1999;Penel et al, 2012), further favorable prognostic factor for survival were the absence of bone or multiple organ metastases, young age, and high histopathologic grade, synovial or liposarcoma histology, radiotherapy, radical metastasectomy, et al The sample size of our cohort was not large enough to detect more predictive factors.…”
Section: 7171 Efficacy and Toxicity Of Chemotherapy With Or Without mentioning
confidence: 99%
See 1 more Smart Citation
“…Performance status is a well-known prognostic factor of metastatic soft tissue sarcoma in general (Van Glabbeke et al, 1999;Maurel et al, 2009;Kroep et al, 2011). In other literature (Van Glabbeke et al, 1999;Penel et al, 2012), further favorable prognostic factor for survival were the absence of bone or multiple organ metastases, young age, and high histopathologic grade, synovial or liposarcoma histology, radiotherapy, radical metastasectomy, et al The sample size of our cohort was not large enough to detect more predictive factors.…”
Section: 7171 Efficacy and Toxicity Of Chemotherapy With Or Without mentioning
confidence: 99%
“…Doxorubicin, first reported to have activity in sarcomas 40 years ago, remains an important first-line treatment of choice for many subtypes, Single -agent doxorubicin is the most widely accepted treatment option for these tumors (Sleijfer et al, 2005). Advanced and metastatic STSs are currently treated by doxorubicin and / or ifosfamidebased regimens at first line ,with an objective response (OR) of 23% to 48% (Maurel et al, 2009). And the rarity and diverse characteristics of sarcomas has impeded the development of new treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to dose intensification by high-dose chemotherapy (HDCT) with the use of PBSC transplantation have raised objective response rates to 20-65%, but failed to show any OS benefit. [1][2][3] However, in some phase I trials using HDCT, long-term survivors have been reported. 4 In patients with germ cell cancer (GCC) resistant to platinum-based chemotherapy, the therapeutic outcome is also very poor.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced and metastatic STSs are currently treated by doxorubicin and/ or ifosfamide-based regimens at first line setting. As a first line therapy, combination therapy of both drugs accounts for an objective response (OR) of 23% to 48% (Schutte et al., 1990;Edmonson et al, 1993;Santoro et al, 1995; Le Cesna et al, 2000;Maurel et al, 2009 …”
mentioning
confidence: 99%